Scena Illustrata, Il volo al polo nord - Unknown (Massachusetts Institute of Technology. Libraries. Department of Distinctive Collections, 1897)
Italian newspaper with a front page article about S.A. Andreé's expedition to the North Pole, with an illustration of a balloon flying over icy water. For more information about this item, visit https://archivesspace.mit.edu/repositories/2/digital_objects/759